DEVELOPING ENGLISH LESSON PLAN AND STUDENTS’ WORKSHEET USING PROBLEM BASED LEARNING IN TEACHING WRITING DESCRIPTIVE TEXTS FOR THE FIRST YEAR STUDENTS OF SMP - Tiana, Elfa; Prawati, Atni; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research was aimed to develop and to find out the validity level of English instructional tools (lesson plan and students’ worksheet) by using Problem Based Learning as one of learning models suggested in the 2013 Curriculum.. The research design is developmental research design applied which 4D model by Thiagarajan (1974). To develop English instructional tool, there were three stages involved in this research, (a) defining stage which is done to set and define the product development requirements, (b) designing stage which is done to plan the draft of instructional tool and arranged it into the right format and (c) developing stage which is done to modify and validate the instructional tool. In order to find out the validity level of developing English instructional tools, the data were collected by using validation sheet of lesson plan and students’ worksheet. The English instructional tools, then validated by experts. Based on data analysis, the validation score of lesson plan is 91,61% and the validation score of students’ worksheet is 92,01%. Those results showed that the instructional tools in the form of lesson plan and students’ worksheet were very valid. They can be fully implemented in writing classroom.Key Words: Developing, Lesson plan, Students’ Worksheet, Problem Based Learning, Writing, Descriptive Texts,